2013
DOI: 10.1161/circresaha.113.301077
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery and Characterization of Alamandine

Abstract: n the past few years, novel components of the renin-angiotensin system (RAS) have been described, including the prorenin/ renin receptor, 1 angiotensin-converting enzyme-2 (ACE2), 2,3 and Mas.4 ACE2 and Mas are now considered to be part of a novel axis of the RAS, the ACE2/angiotensin 1 to 7 [Ang-(1-7)]/Mas axis, 4-11 which counteracts most of the action of the classical Rationale: The renin-angiotensin system (RAS) is a key regulator of the cardiovascular system, electrolyte, and water balance. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
285
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(303 citation statements)
references
References 30 publications
7
285
2
9
Order By: Relevance
“…Contrarily, other reports have shown that AT2 deficiency does not affect Ang II-induced AAA in LDL -/-mice while PD123319 augments AAA through a mechanism that is AT2 receptor independent [59]. Such conflicting data could be explained by the different backgrounds of the used animals and the poor selectivity of PD123319, since this compound can also block the MrgD receptor for alamandine [60].…”
Section: Renin Angiotensin System -Classical Systemmentioning
confidence: 94%
“…Contrarily, other reports have shown that AT2 deficiency does not affect Ang II-induced AAA in LDL -/-mice while PD123319 augments AAA through a mechanism that is AT2 receptor independent [59]. Such conflicting data could be explained by the different backgrounds of the used animals and the poor selectivity of PD123319, since this compound can also block the MrgD receptor for alamandine [60].…”
Section: Renin Angiotensin System -Classical Systemmentioning
confidence: 94%
“…Namely, Santos et al demonstrated that Ang-(1-7) is the ligand for the G-protein-coupled receptor Mas, and that the ACE2-Ang-(1-7)-Mas axis is the counter-regulating of the actions of classical RAS [4,5]. Also, a variety of biologically active peptides, novel components of the RAS have been found recently: proangiotensin-12 (angiotensin-(1-12)) [6], angiotensin A (Ang A) [7,8] and alamandine [9,10].…”
Section: Short Overview Of the Rasmentioning
confidence: 99%
“…By hydrolyzing the C-terminal amino acid of Ang A by ACE2, or decarboxylation of N-terminal aspartate of Ang-(1-7) into alanin, alamandine is produced [51]. Alamandine produced several biological effects including endothelial-dependent vasorelaxation in aortic rings of mice and rats or central cardiovascular effects.…”
Section: Ace2/ Ang-(1-7)/ Mas Axismentioning
confidence: 99%
“…Alamandine produced several biological effects including endothelial-dependent vasorelaxation in aortic rings of mice and rats or central cardiovascular effects. Microinjection of alamandine into rostal ventrolateral medulla (RVLM) increased blood pressure, and microinjection into caudal ventrolateral medulla (CVLM) decreased blood pressure, and modulated the baroreflex sensitivity after intra-cerebro ventricular (ICV) infusion [51]. Masrelated G-coupled receptor type D (MrgD) has been identified as the receptor for alamandine [51].…”
Section: Ace2/ Ang-(1-7)/ Mas Axismentioning
confidence: 99%